2020
DOI: 10.1186/s12935-020-01521-3
|View full text |Cite
|
Sign up to set email alerts
|

Circ_0004913 sponges miR-1290 and regulates FOXC1 to inhibit the proliferation of hepatocellular carcinoma

Abstract: Background: Circular RNA (circRNA), an novel type of non-coding RNA, could interact with miRNA and protein molecules to regulate the occurrence and progression of hepatocellular carcinoma (HCC). However, little is known about the pathogenesis of circ_0004913 in HCC. Materials: Through the GEO (Gene Expression Omnibus database) to find dysfunctional circRNAs in HCC, and circ_0004913 was selected as the research object. Quantitative reverse transcription PCR (qRT-PCR) was used to detect the expression level of c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…High expression of circ 0004913 was found to be linked with a longer OS in all HCC patients [ 44 ]. One study has found that circ 0004913 sponges miR-1290 and regulates FOXC1 to inhibit the proliferation of HCC [ 45 ]. Zhou et al found that circ 0001806 promotes HCC development through the miR-193a-5p/MMP16 axis [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…High expression of circ 0004913 was found to be linked with a longer OS in all HCC patients [ 44 ]. One study has found that circ 0004913 sponges miR-1290 and regulates FOXC1 to inhibit the proliferation of HCC [ 45 ]. Zhou et al found that circ 0001806 promotes HCC development through the miR-193a-5p/MMP16 axis [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…This study contributed to the development of circRNAs as diagnostic or therapeutic targets across cancer types. [44,45] The Cancer Genome Atlas (TCGA) Proliferation, migration, and invasion [25] Proliferation, colony formation, migration, invasion, and EMT [24] Proliferation, migration, and invasion [36] Proliferation, colony formation, cell cycle, and radiosensitivity [37] Proliferation, migration, and invasion [41] Proliferation, invasion, and apoptosis [29] Proliferation and apoptosis [38] Proliferation, migration, invasion, and apoptosis [39] Proliferation, migration, and invasion [32] Proliferation, invasion, migration, and glycolysis [40] Proliferation and invasion [19] Proliferation, migration, invasion, apoptosis, and EMT [34] Proliferation and colony formation [17] Proliferation, migration, and cell cycle [26] Proliferation and migration [21] Proliferation, metastasis, and glycolysis [20] Proliferation, migration, invasion, and apoptosis [31] BC: Bladder cancer; CC: Cervical cancer; ceRNA: Competing endogenous RNA; EC: Esophageal cancer; EMT: Epithelial-mesenchymal transition; GC: Gastric cancer; HCC: Hepatocellular carcinoma; LC: Lung cancer; LSCC: Laryngeal squamous cell cancer; LUAC: Lung adenocarcinoma; miRNA: MicroRNA; mRNA: Messenger RNA; PTC: Papillary thyroid cancer; TC: Thyroid cancer; -: Not available. analysis of PRKCI genes demonstrated amplification in more than 20% of clinical squamous cell carcinoma samples, correlated with decreased OS.…”
Section: Discussionmentioning
confidence: 99%
“…We found that circPRKCI could regulate progression in various cancers via ceRNA mechanism. [31,38] Only a few studies reported that circPRKCI modulates cancer progression via interacting with RBPs. For example, circPRKCI can bind to FXR1 protein competitively and block the formation of FXR1/PRKCI complex, thereby reducing cell invasion and drug resistance of NSCLC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, the inhibitory effect of miR-1290 on Forkhead box C1 (FOXC1) is removing, and the expression of FOXC1 increased. 83 The expression of cir-cBRAF is downregulated in tissue and cell line of glioma, and its dysregulation is correlated with tumor size, WHO grade, and low survival rate of patients. CircBRAF could serve as a molecular sponge for miR-1290 to elevate the expression of miR-1290 target genes.…”
Section: Interaction Of Mir-1290 With Other Noncoding Rnasmentioning
confidence: 99%